Desmond the dog detective; the case of the lone stranger. - Best, Herbert, 1894-1981.; Obligado, Lilian (New York, Viking Press, 1962)
A series of robberies, a mysterious lone stranger, and a big black sedan lead Desmond and his master, Gus, to investigate.
Keywords: Mystery and detective stories